Pembuatan Content Management System Website Pengajuan Kegiatan Organisasi Menggunakan Framework Express Js Dan React Js - Renzha, Abraham; Marna Putra, Zagita; Achmad, Andita Dani (Jurnal INSYPRO (Information System and Processing), 2025)
Fajar University's (UNIFA) adoption of contemporary technology demonstrates the necessity of an improved digital information system for the administration of student activities. Workflows that are now done by hand are laborious and prone to errors. The purpose of this research, "Creating a Content Management System for a Website for Submitting Organizational Activities Using the Express.js and React.js Framework," is to improve student involvement, develop an effective content management system, and make material updating easier. Literature studies, observation, and interviews are examples of research methodologies. It has been demonstrated that utilizing Express.js and React.js in CMS development can improve activity management efficiency by facilitating online proposal submission and approval. System testing revealed strong functionality and encouraging user feedback. Based on testing with fourteen users, the system has a 93% success rate, expedites the approval process, and lowers errors. Additionally, system upkeep and staff training are done to guarantee efficacy and ongoing improvement.